The role of working memory and sustained attention in explanatory inference generation - Barreyro, Juan Pablo (2017)
The aim of this work was to study the relationship between working memory, sustained attention and explanatory inference generation in expository texts comprehension. To this end, 120 undergraduate students read two expository texts from natural sciences and completed an inference generation questionnaire, along with four verbal working memory tasks and two sustained attention tasks. The results showed that the executive component of verbal working memory has a direct effect on inference generation, while sustained attention and information storage in verbal working memory have an indirect effect mediated by the executive component. This supports the idea that individual differences in inference generation are related to individual differences in working memory, and also to individual differences in the ability to sustain attention.